Conceptual model of professional orientation of the population in regard to the profession of an “investigator” - N. E. Miloradova (Law and Safety)
The main approaches to constructing a conceptual model of professional orientation of the population regarding the choice of an investigator’s profession have been provided. It has been noted that the productivity of the offered model is provided by modern principles and approaches of career guidance. Among the main approaches the author has defined: socio-economic, psycho-physiological, psycho-pedagogical and differentiated approaches.